Tradisi Kenduri Kematian di Desa Kampung Baru, Kabupaten Katingan - Muhammad Nurul Fadillah; Harles Anwar; Siti Zainab (Syams, 2020)
AbstractThis article aims to analyze the da’wah message in the tradition of death (kenduri) in the village community of Kampung Baru, Katingan Regency. The authors uses qualitative methods. Data obtained in three ways, namely: observation, interviews, and document study. Based on the analysis of the data obtained, this paper concludes that the da'wah message in the tradition of death feasts in Kampung Baru is conveyed in three ways. First, through the food symbol, the message conveyed is related to the message to always pray for fellow humans, nature, all of Allah's creation, to humble oneself, to take lots of care, to love the motherland, to be devoted to both parents, and to always remember death. Second, through verbal delivery related to messages so that humans speak kind and polite words. Third, through nonverbals related to the message that humans are virtuous, carry out Islamic law, such as dress, behavior and actions.